Validasi Metode Penetapan Kadar Dehidrolovastatin Dalam Plasma In Vitro Dengan KCKT - Hariyanto, Gogok; Kardono, L. Broto Sugeng; Mansyur, Umar (UI Scholars Hub, 2008)
Statins are antihyperlipidemic drugs for lowering LDL-cholesterol level in human blood. They were designed to inhibit HMG CoA reductase in the liver so that the enzyme will not catalyze the transformation of HMG CoA into early precursor of LDL-cholesterol. Dehydrolovastatin is a kind of statins whose structure is analogous to lovastatin (its starting material). The aim of this study was to validate method for in vitro analysis of dehidrolovastatin in plasm. The validation included studies of calibration curve and linearity, LLOQ and selectivity, accuracy, precision, recovery,and stability. Dehidrolovastatin was deteminated by Knauer ® HPLC using UV 2500 detector, Kromasil ® 100-5, C18, 250 mm, 4.6 mm i.d., column. Reversed phase was applied with the optimal condition such as mobile phase acetonitrile and phosphoric acid 0.1 % (75:25), the flow rate of 1.2 mL. minutes -1, simvastatin as internal standard and wavelength 238 nm. Concentrations of sample ranged from 0.013 to 0.200 ppm with correlation coefficient of the calibration curves 0,998 and lower limit of quantitation was 0.013 ppm. The results of validation studies fulfilled standard criteria.